ANTIBACTERIAL ACTIVITY OF ANNONA SQUAMOSA L. AND ANNONA RETICULATA L. AGAINST CLINICAL ISOLATES OF MUTANS STREPTOCOCCI THE CAUSATIVE AGENTS OF DENTAL CARIES - Salman, Hamzah Abdulrahman; R, Senthilkumar (Asian Journal of Pharmaceutical and Clinical Research, 2015)
ABSTRACT Objective: Evaluation of antibacterial activity of Annona squamosa L and Annona reticulata L against Streptococcus mutans and Streptococcus sobrinus (mutans streptococci MS) the causative agent of dental caries. Methods: Leaves and bark of A. squamosa and A. reticulata were collected and extracted by methanol solvent using soxhlet apparatus. Clinical samples were isolated from dental caries subjects, and identified by 16S rDNA sequencing. The isolates were tested to study the antibacterial activity of A. squamosa and A. reticulata leaves and bark by disc diffusion method. 5 mg, 10 mg, 15 mg, 20 mg, 25 mg, 30 mg, 35 mg, 40 mg, 45 mg, 50 mg, and 100 mg concentration of the extract were used to study the antibacteial activity of S. mutans and S. sobrinus. Ampicillin (AMP) 10 Î¼g was used as a positive control in all the species. Results: The isolates were identified based on 16S rDNA sequencing as two Streptococcus mutans and two Streptococcus sobrinus. A. squamosa bark showed antibacterial activity against MS species, while, at 100 mg concentration leaves extract of A. squamosa did not show any inhibition against MS species. However, no inhibitory activity being shown in A. reticulata (leaves and bark) against MS species. The result indicates that S. sobrinus is more susceptible to the A. squamosa bark extract than S. mutans. Not much difference showed between the species in regards of different concentration. Conclusion: A. squamosa bark showed antibacterial activity against MS species, further investigation of the A. squamosa bark should be studied to determine the anti-caries properties. Keywords: Annona squamosa, Annona reticulata, Plant extract, Dental caries, Mutans Streptococci, Antibacterial susceptibility testing, 16S rDNA sequencing.